Integrated Bridge Assessment Using TLS and Load Rating: Case Study of Citarum Baru Bridge - Pratama, Dandi Haniif; Astor, Yackob; Widiyaningsih, Yulia; Wusqo, Urwatul (ASTONJADRO, 2026)
Bridges are critical components of transportation infrastructure that support mobility, economic activity, and public safety. Continuous exposure to traffic loads, environmental effects, and material aging requires regular inspection and evaluation to ensure structural performance and serviceability. This study assesses the Citarum Baru Bridge by integrating Load Rating Analysis using the Rating Factor (RF) approach with Terrestrial Laser Scanner (TLS)-based inspection. Structural capacity was evaluated using the Factored Load Method in accordance with national bridge design standards and technical guidelines. Numerical modeling was conducted using CSI SAP2000 v.14 to simulate structural behavior and calculate RF values for critical bridge components. The results show that the Citarum Baru Bridge remains structurally safe, with RF values exceeding 1 for all evaluated elements. Diagonal trusses (A1), longitudinal girders (A2), transverse girders (A3), and diaphragms (A4) and (A5) demonstrate adequate load-carrying capacity under factored loading conditions. Nevertheless, visual inspection and high-resolution TLS data identified moderate structural deterioration, including surface defects and minor geometric deviations. Based on these observations, the bridge was assigned a Condition Rating of 3, indicating satisfactory performance but a clear need for scheduled maintenance. In conclusion, integrating TLS-based inspection with Load Rating Analysis improves assessment accuracy, maintenance planning, service life, and safety.